20.1k views
4 votes
PLZZZZZZZZZZ HELLLPPPPP ASAPPPL

PLZZZZZZZZZZ HELLLPPPPP ASAPPPL-example-1
User Dalelane
by
4.8k points

1 Answer

3 votes

Answer:

The equation to find
x is
(5\cdot x - 2)^(\circ) + (2\cdot x -2)^(\circ) + x^(\circ) = 180^(\circ).

The degree measure of each angle is:
m\angle J = 113^(\circ),
m\angle K = 44^(\circ) and
m\angle L = 23^(\circ).

Explanation:

From Euclidean Geometry we remember that the sum of internal angles in triangles equals 180°. If we know that
m\angle J = (5\cdot x -2)^(\circ),
m \angle K = (2\cdot x - 2)^(\circ) and
m\angle L = x^(\circ), then we construct the following equation of the triangle JKL in function of
x:


m\angle J + m\angle K + m\angle L = 180^(\circ) (1)


(5\cdot x - 2)^(\circ) + (2\cdot x -2)^(\circ) + x^(\circ) = 180^(\circ)


8\cdot x -4 = 180^(\circ)


8\cdot x = 184


x = 23

Finally, the measure of each angle is, respectively:


m\angle J = (5\cdot x -2)^(\circ)


m\angle J = 113^(\circ)


m \angle K = (2\cdot x - 2)^(\circ)


m\angle K = 44^(\circ)


m\angle L = x^(\circ)


m\angle L = 23^(\circ)

User Picaso
by
4.0k points